Wear loss of stir cast aluminium alloy 8011. (2020) - Magibalan, S.; Senthil Kumar, P.; Balan, A.V.; Shivasankaran, N.; Sankar, S.P.; Prabu, M.; Saravanan, S.
Abstract: The dry sliding wear loss behavior of AA 8011 matrix composite manufactured by stir casting process was considered. A regression model was established to predict the wear loss of the prepared composite. The wear test was steered with pin-on-disc apparatus with the controlling three-factor, three-level central composite rotatable design matrix was used to minimize the parameters were, applied load of 5, 10, 15 N and sliding velocity of 1.5, 3, 4.5 m/s with interval of 5, 10, 15 min at running time. A statistical investigation of wear test was shown using RSM under the DOE with Regression Equation using MINITAB 17 software.